Pengaruh Content Marketing Dan Online Customer Review Terhadap Keputusan Pembelian Produk Kecantikan Pada Followers Akun Instagram @Sociolla - Sari, Dina Merlinda; Pratiwi, Ni Made Ida; Maduwinarti, Ayun (Research Journal of Social Science and Economics, 2025)
The company operates through a website. After experiencing sharp declines in the second and third quarters of 2020, monthly visits to the Sociolla Indonesia website increased to around 3.1 million in the fourth quarter of that year. Data from Social Bella Indonesia shows that there has been an increase in spending in the East Java region by 23 percent from 2019 to 2021, indicating that this organization always pays attention to the beauty needs of beauty activists in Indonesia. The purpose of this study was to see the effect of Content Marketing on the choice of buying superior goods for Instagram @Sociolla account supporters, the effect of Online Customers Reviews on purchasing decisions [beauty products on @Sociolla Instagram account followers, and the impact of Content Promotion and Online Customer Surveys on purchasing decisions beauty products on followers of the Instagram account @Sociolla. This study uses a quantitative research method that presents research results in a descriptive manner using statistical figures. Based on the research findings, the decision to purchase beauty products by Instagram Sociolla followers is not influenced by online customer reviews, while the decision to purchase beauty products by Instagram Sociolla followers is positively and significantly influenced by content marketing. c